Video Journal of Education and Pedagogy - White, E. Jayne; Peters, Michael; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
As of the 1st September 2018, the Video Journal of Education and Pedagogy will be published by the Association of Visual Pedagogies. The journal has now ceased to accept submissions via the SpringerOpen submission system, and can be viewed on Brill's website: https://brill.com/view/journals/vjep/vjep-overview.xml .
Keywords: Learning, Psychology of; Teachers$1 (BTraining of.s; Emigration and immigration$1 (BSocial aspects.s; Education; Instructional Psychology; Teaching and Teacher Education; Sociology of Migration; Education